Evolutionary gain and loss of a plant pattern-recognition receptor for HAMP recognition - Simon Snoeck; Bradley W Abramson; Anthony GK Garcia; Ashley N Egan; Todd P Michael; Adam D Steinbrenner (eLife, 2022)
As a first step in innate immunity, pattern recognition receptors (PRRs) recognize the distinct pathogen and herbivore-associated molecular patterns and mediate activation of immune responses, but specific steps in the evolution of new PRR sensing functions are not well understood. We employed comparative genomic and functional analyses to define evolutionary events leading to the sensing of the herbivore-associated peptide inceptin (In11) by the PRR inceptin receptor (INR) in legume plant species. Existing and de novo genome assemblies revealed that the presence of a functional INR gene corresponded with ability to respond to In11 across ~53 million years (my) of evolution. In11 recognition is unique to the clade of Phaseoloid legumes, and only a single clade of INR homologs from Phaseoloids was functional in a heterologous model. The syntenic loci of several non-Phaseoloid outgroup species nonetheless contain non-functional INR-like homologs, suggesting that an ancestral gene insertion event and diversification preceded the evolution of a specific INR receptor function ~28 my ago. Chimeric and ancestrally reconstructed receptors indicated that 16 amino acid differences in the C1 leucine-rich repeat domain and C2 intervening motif mediate gain of In11 recognition. Thus, high PRR diversity was likely followed by a small number of mutations to expand innate immune recognition to a novel peptide elicitor. Analysis of INR evolution provides a model for functional diversification of other germline-encoded PRRs.